Radiation therapy for gastric cancer - Vázquez, Tabaré (Cirugía del Uruguay, 1988)
The treatment of gastric neoplasms presents various problems for the radiation therapist. Stomach it is a mobile, compliant organ that develops distinct and critical roles within the gastrointestinal tract, namely deposition, crushing, absorption of food and production of acid and hormones.